TATA KELOLA PENANGGULANGAN PASCA BENCANA DI KECAMATAN BAYAH - Hilman Padhlullatif (Jurnal Manajemen Bencana (JMB), 2023)
Bayah is one of the sub-districts in the southern part of Lebak which has a fairly wide and beautiful coastline.This proves that there are several tourist spots in it. Among them are sawarna beach,pulo manuk beach and othersIn addition,bayah is also often hit by natural disasters such as flash floods,landslides, earthquakes and also the risk of tsunamis.because here there are several rivers and also the coast of the Indian Ocean. The area is directly facing one of the sources of triggers for the greatest potential for natural disasters in the world, namely the megathrust of the subduction zone of active tectonic plates of Indo-Australia and Eurasia.This article will explain the results of the identification and analysis of the level of vulnerability to natural disasters. With research fokus on post-disaster management governance agains of bayah, Lebak regency, Banten. The research method used is qualitative research, which is a research process that provides understanding based on methods that are in the nature of investigating a social phenomenon that exists in society. The level of threat to people living in disaster-prone areas in order to increase vigilance to avoid the risk of natural disaster cases that are most often encountered in bayah district namely floods,landslides,earthquakes and land movements.The level of vulnerability to natural disaster hazards is in the moderate to high category. The level of regional capacity in dealing with natural disasters belongs to the moderate category. In this case of course,there are post-disaster objects that need to be traced.